2015
DOI: 10.5433/1679-0359.2015v36n1p39
|View full text |Cite
|
Sign up to set email alerts
|

Resíduos agrícolas e argila expandida no cultivo da orquídea Oncidium baueri Lindl

Abstract: ResumoPara o cultivo de orquídeas em recipientes é fundamental a seleção do substrato correto, visto que este influenciará a qualidade do produto final, servindo como suporte ao sistema radicular das plantas. O presente trabalho teve como objetivo avaliar diferentes resíduos agrícolas e argila expandida no cultivo da orquídea Oncidium baueri Lindl. As plantas foram submetidas aos tratamentos: casca de pinus + casca de arroz carbonizada; casca de pinus + casca de café; casca de pinus + fibra de coco; casca de n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 16 publications
0
4
0
2
Order By: Relevance
“…Coffee husk is rich in organic compounds and other elements such as caffeine and tannins (PANDEY et al, 2000). It has the potential to be used as a substrate for orchid cultivation (ASSIS et al, 2011;MORA et al, 2015), providing benefits to nature, such as its use in production areas. Assis et al (2011) observed that coffee husk mixed with coconut powder or carbonized rice husk can be used in the cultivation of the hybrid (C. forbesii x C. labiata) x C. labiata, not being indicated as a single substrate.…”
Section: Coffee Huskmentioning
confidence: 99%
See 3 more Smart Citations
“…Coffee husk is rich in organic compounds and other elements such as caffeine and tannins (PANDEY et al, 2000). It has the potential to be used as a substrate for orchid cultivation (ASSIS et al, 2011;MORA et al, 2015), providing benefits to nature, such as its use in production areas. Assis et al (2011) observed that coffee husk mixed with coconut powder or carbonized rice husk can be used in the cultivation of the hybrid (C. forbesii x C. labiata) x C. labiata, not being indicated as a single substrate.…”
Section: Coffee Huskmentioning
confidence: 99%
“…Assis et al (2011) observed that coffee husk mixed with coconut powder or carbonized rice husk can be used in the cultivation of the hybrid (C. forbesii x C. labiata) x C. labiata, not being indicated as a single substrate. On the other hand, for Oncidium baueri, Mora et al (2015) described that mixtures of pine bark with coffee husk and coconut fiber provided favorable results in the cultivation.…”
Section: Coffee Huskmentioning
confidence: 99%
See 2 more Smart Citations
“…De acordo com Mora et al (2015), a compostagem é uma técnica utilizada para se obter rápida estabilização da matéria orgânica e atribuir melhores condições para o seu uso na agricultura. O processo de compostagem consiste em utilizar matérias-primas com uma relação carbono/nitrogênio (C/N) favorável ao metabolismo dos microrganismos decompositores e facilitar a decomposição dessa matériaprima por meio do controle das condições ambientais, como umidade, aeração e temperatura (VALENTE et al, 2009;ASSIS et al, 2011).…”
Section: Introductionunclassified